Management of Foreign Teachers in International Educational Institutes in Thailand - Putthithanasombat, Phramaha Min; Walsh, John (Journal of Education and Vocational Research, 2013)
This paper seeks to determine methods and approaches of managing international English language teachers in Thailand in the context of the forthcoming ASEAN Economic Community. Qualitative interviews, focus group and ethnographic observation were used to obtain data. The research shows that schools involved adopt pragmatic approaches to teacher recruitment and management but retain elements of the longstanding paternalistic Thai approach to management of human resources. The research is limited to two research study sites and to a specific time period. Issues are raised concerning the approach of potential international teachers and the means of obtaining employment. The lack of meaningful preparation for the ASEAN Economic Community in the education sector in Thailand is made evident. Management of international school English language teachers in Thailand has been only lightly researched previously and is partly remedied here.